In silico Computational Analysis of Siddha Formulation Veppampoo mathirai in Inhibition of Angiotensin-Converting Enzyme Receptor Target against Hypertension - Chitra, Dr. S. M. (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Hypertension (HTN) is a leading non-communicable disease in the world which affects most people. Even though, modern medicines are available widely, people show their interest to take traditional system of medicines like Siddha to overcome some untoward side effects. In this regard, Veppampoomathirai, a polyherbal siddha formulation prescribed for HTN was studied by in silico computational analysis for its potential action against HTN in inhibition of Angiotensin-converting enzyme receptor target compared with standard captopril drug of modern medicine. Materials and Methods: The phytochemicals present in the formulation were identified, selected, and retrieved through literature survey. Molecular docking analysis was performed by AutoDock tool version 4. The lead molecules were identified by their binding affinity toward target enzyme angiotensin-converting enzyme (ACE) and compared with standard captopril. Results: The phytoprinciples such as Ascorbic acid, Elemene, Cinnamaldehyde, Gallic Acid, Nimbiol, Piperic acid, Piperine, Eugenol, Nimbolide, Rutin, and Solasodine had 7–10 interactions with more interaction surface area. Nimbiol and Gallic acid had ten interactions, whereas Piperic acid, Peperine, and Nimbolide had nine interactions which are higher than the standard Captopril with the active amino acids at the target ACE enzyme. Conclusion: The study concludes that the formulation Veppampoomathirai has potential binding action against ACE target enzyme that helps in reducing blood pressure.